1990
DOI: 10.3109/00016349009021040
|View full text |Cite
|
Sign up to set email alerts
|

Stress Urinary Incontinence And Posterior Bladder Suspension Defects: Results Of Vaginal Repair Versus Burch Colposuspension

Abstract: Vaginal repair has been recommended in cases of stress urinary incontinence and posterior bladder suspension defect diagnosed by colpocysto-urethrography. Thirty-eight women with stress urinary incontinence and posterior suspension defect have been treated. First, 19 women underwent a vaginal repair. In a second period, another 19 consecutive patients had a colposuspension a.m. Burch. The patients have been evaluated 6 months postoperatively and at a long-term follow-up. No significant difference was found pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Studies describing results over longer periods are rare. Success rates after surgery seem to be inversely related to the length of postoperative follow-up [5,6,8]. In the present Demirci/Yucel/Eren/Alkan/Demirci/ Yıldırım study, the overall cure rate was 87.7% for 1.5 years and 77.4% for 4.5 years of follow-up.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Studies describing results over longer periods are rare. Success rates after surgery seem to be inversely related to the length of postoperative follow-up [5,6,8]. In the present Demirci/Yucel/Eren/Alkan/Demirci/ Yıldırım study, the overall cure rate was 87.7% for 1.5 years and 77.4% for 4.5 years of follow-up.…”
Section: Discussionmentioning
confidence: 49%
“…However, 5 years after the procedure only 75.8% of the women were symptom-free. Thunedborg et al [6] reported a complete cure rate of 78.6% for 6 years, Kinn [9] reported 78% for 5 years, Eriksen et al [8] reported 67% for 5 years, Lebret et al [10] reported 64% for 5 years, Kjolhede and Ryden [11] reported 63% for 6 years and Christensen et al [12] reported 33%. These earlier and long-term results are comparable with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Failure rates were used to compute odds ratios not computed by the original studies. For some studies the success rates and odds ratios in the primary studies [29-32] differed from those reported by Ioannidis et al [13] or the meta-analysis [28]. When there was a discrepancy, we used the rates reported in the primary studies.…”
Section: Resultsmentioning
confidence: 99%
“…Confounding was more likely in two studies because subjects on one treatment were treated several years previously compared with subjects on another. Confounding was also more likely in other studies (the majority of trials of labor and surgery for incontinence and half the studies of early discharge [32,33]) because treatment was allocated on the basis of patient characteristics likely to influence the possibility of treatment failure. Confounding may have been less likely if the physicians treating the patients used only one procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation